Level of Nomophobia (No Mobile-Phone Phobia) in Nursing Students of Itkes Wiyata Husada Samarinda: A Descriptive Study - Siti Kholifah; Idham Khalid; Rusdi Rusdi (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2020)
Introduction: Nomophobia (no mobile-phone phobia) is a situational anxiety faced by students if they do not use a smartphone. Students who have a high level of nomophobia will always feel excessive anxiety because they are very dependent on smartphones. The aim of this study is to descript of the level of nomophobia among nursing students of ITKes Wiyata Husada Samarinda.Method: The reasearch was employed a descriptive design with survey approach. The population was 317 nursing students level I, II and III at ITKes Wiyata Husada Samarinda in the 2019/2020 academic year. The research sample was 177 respondents with proportionate random sampling technique. The questionnaire used is NMP-Q (Nomophobia Questionnaire). The data then analyzed by using univariate.Results: The study showed that 89 respondents (50.3%) had a high level of nomophobia and 88 respondents (49.7%) had a low level of nomophobia. The dimensions of nomophobia experienced by students felt unable to communicate as many as 64 respondents (36%), fear and feeling uncomfortable 48 respondents (27%), unable to access information 35 respondents (20%) and lost signals of 30 respondents (17%).Conclusion: Half of the nursing students of ITKes Wiyata Husada Samarinda experience a high level of nomophobia which tends to the dimension of not able to communicate because smartphones are a tool that makes communication easier without limited by distance and time so that students have high dependency and will feel excessive anxiety if they cannot communicate with smartphones . It is hoped that the Institute can provide education to students related to nomophobia through empowering academic supervisors.